Functional and inhibition studies on 2-oxoglutarate-dependent oxygenases - Thalhammer, A (2012)
This thesis explores roles of 2-oxoglutarate-dependent (2OG) oxygenases as interfaces that modulate steps in the flow of genetic information in cells in response to oxygen availability. Chapter 1 introduces mechanistic, biochemical and physiological aspects of major subfamilies of 2OG oxygenases, and their established regulatory roles in cells. In addition, structural and functional aspects of the ribosome and the translation process are discussed, with a focus on post-translational ribosome modifications. Chapter 2 investigates histone demethylases, which mediate chromatin-dependent regulation of gene expression and provides proof-of-concept for the rational, structure-guided design of small-molecules for selective inhibition of 2OG oxygenases with roles in cancer and inflammatory disease. Chapter 3 suggests regulatory roles for ten-eleven-translocation (TET)- catalysed DNA hydroxylation; calorimetric and thermal analyses reveal a duplex-stabilizing effect of the epigenetic 5-methylcytosine mark that is reversed upon conversion to 5- hydroxymethylcytosine (also termed the ‘sixth’ DNA base), raising the possibility that 2OG oxygenase catalysis might affect transcription via biophysical effects. Chapter 4 investigates fluoride release assays as a technology to enable medicinal chemistry studies on 2OG oxygenases with roles in fat mass regulation and obesity, cancer and inflammation; studies on the ALKBH5 enzyme show that it is a hypoxically upregulated 2OG oxygenase with a substrate preference distinct from previously characterized ALKBH enzymes. Chapter 5 identifies OGFOD1 as a 2OG-dependent ribosomal protein hydroxylase. OGFOD1 catalysis is conserved from yeast to humans. OGFOD1 catalyses formation of trans-3- hydroxy-L-proline in a highly conserved loop of ribosomal protein S23 proximal to the ribosomal decoding centre, possibly to modulate the interactions of eukaryotic ribosomes with tRNA, mRNA and translation factors in an oxygen-dependent manner. OGFOD1 is the functionally most well-conserved protein-modifying 2OG oxygenase; likewise, ribosomal protein S23 hydroxylation is the most well-conserved post-translational ribosome modification in eukaryotes. Some cell lines require OGFOD1 for proliferation, and scaffolds for OGFOD1- selective inhibitors are developed for use as potential antiproliferative agents and probes for cellular function. Chapter 6 shows the development of assays to investigate whether OGFOD1 catalysis affects ribosome assembly and function, including processivity, accuracy of initiation, elongation and termination, in yeast and mammalian cell lines. Chapter 7 concludes that ribosome hydroxylation might present an additional layer of regulatory complexity by which 2OG oxygenases could enable cells to respond to fluctuating oxygen levels.